Active tuberculosis case finding interventions among immigrants, refugees and asylum seekers in Italy - Monica Sañé Schepisi; Gina Gualano; Pierluca Piselli; Marta Mazza; Donatella D'Angelo; Francesca Fasciani; Alberto Barbieri; Giorgia Rocca; Filippo Gnolfo; Piefranco Olivani; Maurizio Ferrarese; Luigi Ruffo Codecasa; et al. (MDPI AG, 2016)
In Italy tuberculosis (TB) is largely concentrated in vulnerable groups such as migrants and in urban settings. We analyzed three TB case finding interventions conducted at primary centers and mobile clinics for regular/ irregular immigrants and refugees/asylum seekers performed over a four-year period (November 2009-March 2014) at five different sites in Rome and one site in Milan, Italy. TB history and presence of symptoms suggestive of active TB were investigated by verbal screening through a structured questionnaire in migrants presenting for any medical condition to out-patient and mobile clinics. Individuals reporting TB history or symptoms were referred to a TB clinic for diagnostic workup. Among 6347 migrants enrolled, 891 (14.0%) reported TB history or symptoms suggestive of active TB and 546 (61.3%) were referred to the TB clinic. Of them, 254 (46.5%) did not present for diagnostic evaluation. TB was diagnosed in 11 individuals representing 0.17% of those screened and 3.76% of those evaluated. The overall yield of this intervention was in the range reported for other TB screening programs for migrants, although we recorded an unsatisfactory adherence to diagnostic workup. Possible advantages of this intervention include low cost and reduced burden of medical procedures for the screened population.